2013
DOI: 10.4209/aaqr.2012.06.0162
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Aerosol Parameters Derived from Ground and Satellite Measurements over Varanasi Located in the Indo-Gangetic Basin

Abstract: Atmospheric aerosol plays a very important role in the Earth's radiation budget and global climate studies. This study reports the variability of the physical and optical properties of columnar aerosol and water vapour over Varanasi (25.2°N, 82.9°E), located in the heart of the Indo-Gangetic Basin, for the first time. The study was carried out using a MICROTOPS-II sunphotometer to measure the Aerosol Optical Depth (AOD) and metrological parameters. It is observed that the AOD loading is enhanced during the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…Such a pattern was expected from the previous analysis of the AOD and α values for each month, indicating higher values at shorter wavelengths (440 nm) for postmonsoon and winter compared to pre-monsoon and monsoon. Such evidence is rather characteristic for the IGP sites, as shown in Kanpur and Varanasi (Tiwari and Singh, 2013), but opposite to that found over centralsouth India (Sinha et al, 2012), where the pre-monsoon spectral AOD dominates. In the current analysis, it is shown that the post-monsoon AOD is highest even at 675 nm, highlighting the significant influence of the intense smoke plumes covering nearly the whole IGP in November 2012.…”
Section: Monthmentioning
confidence: 66%
See 1 more Smart Citation
“…Such a pattern was expected from the previous analysis of the AOD and α values for each month, indicating higher values at shorter wavelengths (440 nm) for postmonsoon and winter compared to pre-monsoon and monsoon. Such evidence is rather characteristic for the IGP sites, as shown in Kanpur and Varanasi (Tiwari and Singh, 2013), but opposite to that found over centralsouth India (Sinha et al, 2012), where the pre-monsoon spectral AOD dominates. In the current analysis, it is shown that the post-monsoon AOD is highest even at 675 nm, highlighting the significant influence of the intense smoke plumes covering nearly the whole IGP in November 2012.…”
Section: Monthmentioning
confidence: 66%
“…Due to larger variations in light scattering caused by changes in fine-mode aerosols (Schuster et al, 2006), the monthly variability of AOD 440 is more intense than that at 936 nm, ranging from as low as ~0.3 (March 2010) to as high as ~1.4 (November 2012). More or less similar pattern of the spectral AOD variation has been found over Delhi (Lodhi et al, 2013), Hyderabad (Sinha et al, 2012), Ahmedabad (Ganguly et al, 2006), Dibrugarh (Gogoi et al, 2009), Kullu valley (Guleria et al, 2011), Varanasi (Tiwari and Singh, 2013), Pune (Dani et al, 2012), Bangalore (Vinoj et al, 2004), among many others.…”
Section: Severe Aerosol Loading Over Greater Noidamentioning
confidence: 95%
“…Similar studies have been conducted over northern China by Qi et al (2012), who concluded that the AOD values have significant seasonal variation, specifically small and high in summer. Tiwari and Singh (2013) studies shown that coarse-mode aerosol particles are dominant in the pre-monsoon, while fine-mode aerosol particles are dominant in the winter season. Other studies have been conducted by Kuniyal et al (2009) and Gupta et al (2013), concluded AOD variations were highly dependent on both the travel pathways and the sources (e.g., sea salt, desert dust, smoke from burning biomass, and industrial pollution) of the air masses.…”
Section: Seasonal Variations In Aerosol Optical Depth (Aod)mentioning
confidence: 99%
“…Microtops II provide accurate AOD retrievals and is widely used for ground AOD observations (Morys et al, 2001;Tiwari and Singh, 2013;Otter et al, 2002). Previous calibration reported that the rootmean square differences in AOD from Microtops and corresponding AERONET stations were about ±0.02 at 340 nm (Ichoku et al, 2002).…”
Section: Ground Observationsmentioning
confidence: 99%